Sector heterogeneity and credit market imperfections in emerging markets. (February 2017) - Varela, Liliana
Highlights: Non-tradable and tradable sectors respond asymmetrically to country interest rate shocks in EMs. Non-tradable activities account for the negative response of GDP. Tradable activities are not affected by changes in local credit conditions. This asymmetric sectoral response is absent in developed open economies. Abstract: This paper shows that the impact of country interest rate shocks on emerging markets' economic activities can be associated with credit market imperfections affecting principally non-tradable activities. I present novel evidence documenting that tradable and non-tradable activities respond asymmetrically to changes in credit conditions in emerging markets. I show that country interest rate shocks are amplified through non-tradable activities, and that local credit substantially explains their output growth. Unlike the non-tradable sector, tradable activities are not significantly affected by changes in local credit conditions. To rationalize these findings, I introduce a small open economy model with heterogeneous access to international borrowing that accounts for the asymmetric response of tradable and non-tradable activities.